PERAN TES KEPRIBADIAN STIFIn DALAM MENINGKATKAN KEPERCAYAAN DIRI MAHASISWA BKI - Muhamad Jutana; Agus Ali Adzawafi, AM. Fahrurozi (ADISAM PUBLISHER, 2025)
Self-confidence is a positive attitude that enables individuals to develop positive judgments toward themselves, their environment, and the situations they encounter. In reality, the level of self-confidence varies among individuals low, moderate, or high as experienced by several students of the Islamic Guidance and Counseling (BKI) program. Efforts to enhance self- confidence are aimed at fostering a positive mindset, both personally and socially, to cultivate BKI students who are confident, well integrated, and capable of effectively resolving problems. This study aims to examine the self-confidence of BKI students before taking the STIFIn test, to assess their self-confidence after taking the test, and to identify the role of the STIFIn test in enhancing their self-confidence. The research employed a descriptive qualitative approach, with informants selected using the simple random sampling technique. Data were collected through observation, interviews, and documentation. The results indicate that: (1) Several BKI students initially exhibited low self-confidence, were uncertain of their abilities, faced difficulties in expressing opinions, and tended to feel inferior due to frequent self-comparisons with others; (2) The researcher applied the STIFIn Personality Test approach to help BKI students better understand themselves, including their strengths and weaknesses, and to focus on developing their strengths; (3) The STIFIn Personality Test played a role in enhancing the self-confidence of BKI students. Positive attitudes developed, such as greater self-awareness, an increased sense of self-worth, and a stronger focus on positive aspects. The forms of self-confidence improvement varied among students, including progress in learning, communication, and decision-making